GCSE physics - Duncan, Tom. (London : John Murray, 1986)
The 3rd edition of this textbook, which is now in full colour and in line with the requirements of the National Curriculum and the revised GCSE physics syllabuses.
Includes index.
Keywords: Physics; Physics -- For schools